La montée des îles Aran dans la bibliothèque mondiale, une glocalisation littéraire - Frédéric Barbe (Unité Mixte de Recherche 8504 Géographie-cités, 2014)
At the gate of Galway Bay, the Aran Islands today stand out as one of the highest places in the Irish sightseeing space. At the same time, the archipelago has become one of the most famous parts of the Irish work within the world library. For more than a century, particularly after the publication of John Millington Synge’s founder book in 1907, Aran has evolved as a continuous creative writing workshop, without any state cultural policy. This production of scientific and artistic works has transformed Aran and radically changed its living conditions and its position in the global space. This process having turned into a co-production by both foreigners and natives, the global rise of the humble Aran in the world library reminds us of other paradoxical places within the global library, such as the Lacandon forest or the pays dogon.